Racial Discrimination Reflected in the Figurative Languages of "Audre Lorde's Selected Poems" - Anugrah, Fahmi Bayu (Vivid: Journal of Language and Literature, 2023)
This study aims to find out the types of figures of speech that reflect the life of black people and racial discrimination in three Audre Lorde's poems, entitled; Power, Coal, and The Black Unicorn. The theory used in this research is stylistics by Geoffrey Leech, which focuses on figurative language and also uses the theory of racial discrimination. This study uses a qualitative method and uses a content analysis approach because it uses poetry as data. The result shows from the 14 types of figurative languages, only 8 types were found in the poems; Allusion, Hyperbole, Parallelism, Irony, Personification, Simile, Symbolism, and Euphemism, with a total number of 17 data. Those data broadly have meanings related to the life struggles of back people. After that, the researcher found three kinds of racial discrimination in eight figurative languages namely; direct, indirect, and social life racial discrimination. From the three poems, it seems the poet uses figurative language in each of her poems to illustrate the rights and difficulties she faced and the poems are depictions of racial discrimination that causes struggles in the life of black people.